Ayurveda Management of Bipolar Affective Disorder – A Case Study - A, Anjali; K, Satheesh (International Research Journal of Ayurveda & Yoga, 2022)
Bipolar Affective disorder (BPAD) earlier known as manic depressive psychosis (MDP) is a major psychiatric disorder all around the world, which is mainly characterized by frequent and recurrent episodes of mania, hypomania, and depression. A majority of complete aetiology or pathogenesis of BPAD is unknown. As per Ayurveda, Bipolar affective Disorder shows symptoms as mentioned in unmāda. In unmāda, there is significant impairment in the domains of manas, buddhi, samjnājnāna, smŗti, bhakti, śīla, ćeşţa, as well as ācāra. Many of the nidāna mentioned in unmāda like virudha, duşţa, aśući bhojana, bhaya, mano abhighāta, viśama ćeśţa can be identified as the triggering factors in Bipolar affective Disorder. A 18 year old female presented in the OPD with increased worries especially in the evening, hopelessness regarding her future, increased anger and sadness, occasional impulsivity , symptoms can be merely correlated with kaphajonmāda with anubandha of pitta. Internally she was given medicines to manage her depression and anxiety. She was also advised procedures like takrapāna followed by uttamamātra snēhapāna was done as a śodhana therapy following abhyanga and ūşma sweda. Thereafter virecana, nasya śirodhāra and talapotichil. During this time she was also subjected to meditation and counselling techniques as well.The patient responded satisfactorily to the treatment and her symptoms improved significantly. There was marked reduction in her pessimistic attitude. HAM D scale score before treatment was 21 while it reduced to 10 after treatment. Also the HAM A scale score before treatment was 15 while it reduced to 8 after treatment..